Characterization of recombinant human cytomegaloviruses encoding IE1 mutants L174P and 1-382 reveals that viral targeting of PML bodies perturbs both intrinsic and innate immune responses - Scherer, Myriam; Otto, Victoria; Stump, Joachim; Klingl, Stefan; Müller, Regina; Reuter, Nina; Muller, Yves; Sticht, Heinrich; Stamminger, Thomas (Journal of Virology, 2015)
PML is the organizer of cellular structures termed nuclear domain 10 (ND10) or PML-nuclear bodies (PML-NBs) that act as key mediators of intrinsic immunity against human cytomegalovirus (HCMV) and other viruses. The antiviral function of ND10 is antagonized by viral regulatory proteins such as the immediate early protein IE1 of HCMV. IE1 interacts with PML through its globular core domain (IE1) and induces ND10 disruption in order to initiate lytic HCMV infection. Here, we investigate the consequences of a point mutation (L174P) in IE1CORE, which was shown to abrogate the interaction with PML, for lytic HCMV infection. We found that a recombinant HCMV encoding IE1-L174P displays a severe growth defect similar to that of an IE1 deletion virus. Bioinformatic modeling based on the crystal structure of IE1 suggested that insertion of proline into the highly alpha-helical domain severely affects its structural integrity. Consistently, L174P mutation abrogates the functionality of IE1 and results in degradation of the IE1 protein during infection. In addition, our data provide evidence that IE1 as expressed by a recombinant HCMV encoding IE1 1-382 not only is required to antagonize PML-mediated intrinsic immunity but also affects a recently described function of PML in innate immune signaling. We demonstrate a coregulatory role of PML in type I and type II interferon-induced gene expression and provide evidence that upregulation of interferon-induced genes is inhibited by IE1. In conclusion, our data suggest that targeting PML by viral regulatory proteins represents a strategy to antagonize both intrinsic and innate immune mechanisms.
EVALuna2:8299

Controlled crystal dehydration triggers a space-group switch and shapes the tertiary structure of cytomegalovirus immediate-early 1 (IE1) protein - Klingl, Stefan; Scherer, Myriam; Stamminger, Thomas; Muller, Yves (Acta Crystallographica Section D: Biological Crystallography, 2015)
Cytomegalovirus immediate-early 1 (IE1) protein is a key viral effector protein that reprograms host cells. Controlled dehydration experiments with IE1 crystals not only extended their diffraction limit from 2.85 to 2.3Å resolution but also triggered a monoclinic to tetragonal space-group transition with only minor alterations in the unit-cell parameters. An analysis of the pre-dehydration and post-dehydration crystal structures shows how dehydration rearranges the packing of IE1 molecules to meet the unit-cell constraints of the higher lattice symmetry. The transition from P21 to P43 reduces the number of copies in the asymmetric unit from four to two, and molecules previously related by noncrystallographic symmetry merge into identical crystallographic copies in the tetragonal space group. At the same time, dehydration considerably alters the tertiary structure of one of the two remaining IE1 chains in the asymmetric unit. It appears that this conformational switch is required to compensate for a transition that is assumed to be unfavourable, namely from a highly preferred to a rarely observed space group. At the same time, the dehydration-triggered molecular reshaping could reveal an inherent molecular flexibility that possibly informs on the biological function of IE1, namely on its binding to target proteins from the host cell.
Keywords: free-mounting system; humidity-control device; improved scattering and diffraction; lattice symmetry increase; space-group transition; viral effector protein

Crystal structure of cytomegalovirus IE1 protein reveals targeting of TRIM family member PML via coiled-coil interactions - Scherer, Myriam; Klingl, Stefan; Sevvana, Madhumati; Otto, Victoria; Schilling, Eva-Maria; Stump, Joachim; Müller, Regina; Reuter, Nina; Sticht, Heinrich; Muller, Yves; Stamminger, Thomas (PLoS Pathogens, 2014)
PML nuclear bodies (PML-NBs) are enigmatic structures of the cell nucleus that act as key mediators of intrinsic immunity against viral pathogens. PML itself is a member of the E3-ligase TRIM family of proteins that regulates a variety of innate immune signaling pathways. Consequently, viruses have evolved effector proteins to modify PML-NBs; however, little is known concerning structure-function relationships of viral antagonists. The herpesvirus human cytomegalovirus (HCMV) expresses the abundant immediate-early protein IE1 that colocalizes with PML-NBs and induces their dispersal, which correlates with the antagonization of NB-mediated intrinsic immunity. Here, we delineate the molecular basis for this antagonization by presenting the first crystal structure for the evolutionary conserved primate cytomegalovirus IE1 proteins. We show that IE1 consists of a globular core (IE1CORE) flanked by intrinsically disordered regions. The 2.3 Å crystal structure of IE1CORE displays an all ?-helical, femur-shaped fold, which lacks overall fold similarity with known protein structures, but shares secondary structure features recently observed in the coiled-coil domain of TRIM proteins. Yeast two-hybrid and coimmunoprecipitation experiments demonstrate that IE1CORE binds efficiently to the TRIM family member PML, and is able to induce PML deSUMOylation. Intriguingly, this results in the release of NB-associated proteins into the nucleoplasm, but not of PML itself. Importantly, we show that PML deSUMOylation by IE1CORE is sufficient to antagonize PML-NB-instituted intrinsic immunity. Moreover, co-immunoprecipitation experiments demonstrate that IE1CORE binds via the coiled-coil domain to PML and also interacts with TRIM5? We propose that IE1CORE sequesters PML and possibly other TRIM family members via structural mimicry using an extended binding surface formed by the coiled-coil region. This mode of interaction might render the antagonizing activity less susceptible to mutational escape.
EVALuna2:8238

Crystal Structure of the Extracellular Domain of the Human Dendritic Cell Surface Marker CD83 - Heilingloh, Christiane; Klingl, Stefan; Egerer-Sieber, Claudia; Schmid, Benedikt; Weiler, Sigrid; Mühl-Zürbes, Petra; Hofmann, Jörg; Stump, Joachim; Sticht, Heinrich; Kummer, Mirko; Steinkasserer, Alexander; Muller, Yves (Journal of Molecular Biology, 2017)
Keywords: homotypic interactions; immune co-stimulation and -suppression; structure–function relationships; V-set Ig-domain; X-ray crystallography

Manipulation of charge distribution in the arginine and glutamate clusters of the OmpG pore alters sugar specificity and ion selectivity - Schmitt, Christine; Bafna, Jayesh Arun; Schmid, Benedikt; Klingl, Stefan; Baier, Steffen; Hemmis, Birgit; Wagner, Richard; Winterhalter, Mathias; Voll, Lars (Biochimica Et Biophysica Acta-Biomembranes, 2019)
OmpG is a general diffusion pore in the E. coli outer membrane with a molecular architecture comprising a 14-stranded β-barrel scaffold and unique structural features. In contrast to other non-specific porins, OmpG lacks a central constriction zone and has an exceptionally wide pore diameter of about 13 Å. The equatorial plane of OmpG harbors an annulus of four alternating basic and acidic patches whose function is only poorly characterized. We have investigated the role of charge distribution for ion selectivity and sugar transport with the help of OmpG variants mutated in the annulus. Substituting the glutamate residues of the annulus for histidines or alanines led to a strong reduction in cation selectivity. Replacement of the glutamates in the annulus by histidine residues also disfavored the passage of pentoses and hexoses relative to disaccharides. Our results demonstrate that despite the wide pore diameter, an annulus only consisting of two opposing basic patches confers reduced cation and monosaccharide transport compared to OmpG wild type. Furthermore, randomization of charged residues in the annulus had the potential to abolish pH-dependency of sugar transport. Our results indicate that E15, E31, R92, R111 and R211 in the annulus form electrostatic interactions with R228, E229 and D232 in loop L6 that influence pH-dependency of sugar transport.
CRIS-Team Scopus Importer:2019-08-20
Keywords: E. coli; Ion selectivity; Liposome swelling assay; Porin engineering; Reversal potential; Sugar specificity

Recombinant protein production and purification of SiiD, SiiE and SiiF - Components of the SPI4-encoded type I secretion system from Salmonella Typhimurium - Klingl, Stefan; Kordes, Sina; Schmid, Benedikt; Gerlach, Roman; Hensel, Michael; Muller, Yves (Protein Expression and Purification, 2020)
In humans, Salmonella enterica infections are responsible for a plethora of medical conditions. These include intestinal inflammation and typhoid fever. The initial contact between Salmonella and polarized epithelial cells is established by the SPI4-encoded type I secretion system (T1SS), which secretes SiiE, a giant non-fimbrial adhesin. We have recombinantly produced various domains of this T1SS from Salmonella enterica serovar Typhimurium in Escherichia coli for further experimental characterization. We purified three variants of SiiD, the periplasmic adapter protein spanning the space between the inner and outer membrane, two variants of the SiiE N-terminal region and the N-terminal domain of the SiiF ATP-binding cassette (ABC) transporter. In all three proteins, at least one variant yielded high amounts of pure soluble protein. Secondary structure content and cooperative unfolding were investigated by circular dichroism (CD) spectroscopy. Secondary structure contents were in good agreement with estimates derived from SiiD and SiiF homology models or, in case of the SiiE N-terminal region, a secondary structure prediction. For one SiiD variant, protein crystals could be obtained that diffracted X-rays to approximately 4 Å resolution.
CRIS-Team Scopus Importer:2020-04-17
Keywords: Protein expression; Purification; Salmonella; Type I secretion system (T1SS)

Structural and functional dissection reveals distinct roles of Ca2+-binding sites in the giant adhesin SiiE of Salmonella enterica - Peters, Britta; Stein, Johanna; Klingl, Stefan; Sander, Nathalie; Sandmann, Achim; Taccardi, Nicola; Sticht, Heinrich; Gerlach, Roman G.; Muller, Yves; Hensel, Michael (PLoS Pathogens, 2017)

Structural and functional dissection reveals distinct roles of Ca2+-binding sites in the giant adhesin SiiE of Salmonella enterica - Peters, Britta; Stein, Johanna; Klingl, Stefan; Sander, Nathalie; Sandmann, Achim; Taccardi, Nicola; Sticht, Heinrich; Gerlach, Roman; Muller, Yves; Hensel, Michael (PLoS Pathogens, 2017)